PHILOSOPHY OF INTEREST CENGKEH SALAWAKU TRADITIONAL MALUKU SIWALIMA MUSEUM IN AMBON - Yustus N Kamanasa (CILPA, 2014)
This study aimed to describe : 1 . What are the philosophical values contained in clove ornaments in traditional Salawaku . 2 . Where are the different types and clove flower ornamental motifs placed in a museum in the traditional Salawaku Siwalima Ambon . 3 . How does the process of making and application of traditional ornaments on Salawaku. In this study the authors use a single variable type , ie the type of research that is focused on a problem . As for the focus of the research is the philosophy of clove , subjects in this study is the heritage of art and culture is preserved in the Museum Siwalima Ambon , the object of research is philosophy Salawau ornaments that exist in traditional techniques of data collection by observation , and interviews . In this study, using instruments such as a checklist , a list of questions , and camera . Data analysis techniques by means of collecting data , data reduction , classifying the data , and draw conclusions. From the research it can be concluded that : 1 . Each ornament has a meaning and a value philosophy . Value philosophy contained in clove ornaments can not be separated with art and culture , beliefs , and customs organizations pata Siwa Alifuru spooky island . 2 . Past used clove ornaments for decorating mark on the body . However, the development community is now placed on traditional Salawaku Maluku . 3 . The process of making traditional Salawaku , the process is still traditional and custom events melalakukan also is to go through several stages and produce good and mempuyai Salawaku magical powers .Keywords : Value Philosophy , clove flower , In Traditional Salawaku